Pelarangan Khamr dalam Al-Qur’an dan Adaptasi Ekonomi Masyarakat Madinah: Studi Historis tentang Respons Pasar terhadap Tasyrīʻ Bertahap - Mohammad Tohir Salam (Yayasan Albahriah Jamiah Indonesia, 2026)
The prohibition of alcohol in the Qur’an is an example of the gradual transformation of religious regulations in Medina society, which previously recognized the production, distribution, and consumption of intoxicating beverages. Studies on the alcohol verses have developed from the perspective of Islamic interpretation and law. At the same time, analysis of market responses and economic adaptation mechanisms during the tashrīʻ (law-making) process remains relatively limited. This study aims to analyze the relationship between the stages of alcohol prohibition, changes in people’s economic behavior, and the process of market reorganization in the early Islamic period. The study uses a qualitative literature approach with historical methods, a socio-economic history approach, mawḍūʻī interpretation, and a historical-critical analysis of alcohol verses, hadith, and early Islamic historical sources. The results show a pattern of economic adjustment that occurred along with the development of the stages of alcohol prohibition. The phase of recognizing moral and social risks drove changes in public perception of alcohol commodities. The phase of limiting consumption involves reducing the use of public spaces. The total prohibition phase was met by halting circulation, destroying stocks, and shifting economic activity toward commodities recognized within the Islamic economic framework. Historical data demonstrate a high level of collective compliance, minimal indications of organized economic resistance, and a relatively stable reorganization of market relations. These findings suggest that gradual tashrīʻ served as an instrument of socio-economic change, facilitating the acceptance of new norms while supporting market stability in Medinan society during the early Islamic period.